Metformin Improves Mitochondrial Respiratory Activity through Activation of AMPK - Wang, Yu; An, Hongying; Liu, Ting; Qin, Caolitao; Sesaki, Hiromi; Guo, Shaodong; Radovick, Sally; Hussain, Mehboob; Maheshwari, Akhil; Wondisford, Fredric E.; O’Rourke, Brian; He, Ling (Cell reports (Cambridge), 2019)
Impaired mitochondrial respiratory activity contributes to the development of insulin resistance in type 2 diabetes. Metformin, a first-line antidiabetic drug, functions mainly by improving patients’ hyperglycemia and insulin resistance. However, its mechanism of action is still not well understood. We show here that pharmacological metformin concentration increases mitochondrial respiration, membrane potential, and ATP levels in hepatocytes and a clinically relevant metformin dose increases liver mitochondrial density and complex 1 activity along with improved hyperglycemia in high-fat- diet (HFD)-fed mice. Metformin, functioning through 5′ AMP-activated protein kinase (AMPK), promotes mitochondrial fission to improve mitochondrial respiration and restore the mitochondrial life cycle. Furthermore, HFD-fed-mice with liver-specific knockout of AMPKα1/2 subunits exhibit higher blood glucose levels when treated with metformin. Our results demonstrate that activation of AMPK by metformin improves mitochondrial respiration and hyperglycemia in obesity. We also found that supra-pharmacological metformin concentrations reduce adenine nucleotides, resulting in the halt of mitochondrial respiration. These findings suggest a mechanism for metformin’s anti-tumor effects. [Display omitted] •Clinically relevant metformin dose improves liver mitochondrial respiration in obesity•Pharmacological metformin increases mitochondrial respiration and fission•Supra-pharmacological metformin inhibits mitochondrial activity by ADP reduction•AMPK is required for metformin suppression of liver glucose production The mechanism of metformin action still remains controversial, in particular on mitochondrial activity and the involvement of AMPK. Wang et al. show that pharmacological metformin concentration or dose improves mitochondrial respiration by increasing mitochondrial fission through AMPK-Mff signaling; in contrast, supra-pharmacological metformin concentrations reduce mitochondrial respiration through decreasing adenine nucleotide levels.